Disease activity in pregnancy and postpartum in women with MS who suspended rituximab and natalizumab - Razaz, Neda (Neurol Neuroimmunol Neuroinflamm, 2020)
OBJECTIVE: To evaluate risks of disease reactivity during pregnancy and postpartum following rituximab (RTX) and natalizumab (NTZ) suspension in women with MS. METHODS: An observational cohort study of all women with MS disease onset before childbirth between 2006 and 2017. Women were identified through the Swedish MS Registry, a nationwide clinical register, with substratification into 3 groups: women who suspended RTX and NTZ within 6 months before conception and women who were not treated with any disease-modifying treatment (DMT) within 1 year of conception. The primary outcome was the annualized relapse rate (ARR) during pregnancy and 1 year postpartum. RESULTS: We identified 2,386 women with MS onset before a live birth; of these, 76 women suspended RTX and 53 suspended NTZ, and 457 were untreated within 1 year before conception. In all women, regardless of the treatment type, the ARR declined from 0.05–0.04 prepregnancy to 0.03–0.02 during pregnancy, returning to prepregnancy rates at 3–6 months (0.05) postpartum. In the suspended cohort, 76% (98/129) of women resumed a DMT after delivery. The relapse rate 1 year postpartum was significantly higher in the suspended NTZ women compared with the suspended RTX women (adjusted rate ratio [aRR] 7.65, 95% CI 2.47–23.6) and was lower in the suspended RTX women compared with the untreated women (aRR 0.21, 95% CI 0.08–0.61). CONCLUSION: Disease reactivity during the postpartum period was lower among women with MS who suspended RTX before pregnancy, relative to those who suspended NTZ and untreated women. These findings suggest that RTX may exert long-acting effects on MS disease activity that encompass pregnancy and postpartum periods. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that in patients with MS who were on treatment before pregnancy, RTX reduces clinical disease activity compared with NTZ in the postpartum period.